Omicron strain: nature, risk evaluation, and treatment approach - Faeze Baniyaghoobi; Hooman Taghavi; Ali Moradi; Maryam Feyzollahi; Farshid Alazmani Noodeh (فصلنامه ابن سینا)
Background and aims: The dramatic emergence of a novel SARS-CoV-2 strain as the omicron strain has become a global concern, so the aim of the present study was to evaluate the risk and treatment approach of this strain of coronavirus. Methods: In this review article, printed and electronic articles and texts with the keywords Covid-19, Omicron, Coronavirus, strain, type, and vaccine in the years 2021 and 2022 have been studied. Results: The Omicron strain has so far spread globally in 77 countries. numerous mutations in the receptor-binding domain region of the spike protein, which has surpassed the advanced immunization technologies for anti-Covid vaccines, appear to become a public concern. Conclusion: Covid-19 is a global problem, so inequality in access to Covid-19 vaccines among developed and socio-economically disadvantaged countries may lead to the resurgence of new and deadly variants of the SARS-CoV-2 virus. Although many speculations have been formed in scientific forums about different dimensions of the new Omicron strain, but in this study, an attempt has been made to collect up-to-date and reliable information for the awarenessof the scientific community of the country.